Evangelization from the Inside: Reflections from a Prison Cell - Arias, Mortimer (International bulletin of mission research, 1981)
The military coup in Bolivia on July 17, 1980 initiated a bloody and repressive situation in that country. It brought about the arrest and imprisonment in late August of former Methodist Bishop Mortimer Arias in Cochabamba, Bolivia—along with many other Protestant and Roman Catholic leaders, as well as countless lesser-known individuals. After thirty-seven days—during which time little was known by his family, friends, and church of his whereabouts and condition—Dr. Arias was suddenly released by the Bolivian authorities on condition that he leave the country immediately.Born in Uruguay, Mortimer Arias served as bishop of the Evangelical Methodist Church in Bolivia, and as executive secretary of the Council of Methodist Churches in Latin America, with offices in La Paz, Bolivia. Widely respected for his leadership in the ecumenical movement, Dr. Arias gave a memorable plenary address at the Fifth Assembly of the World Council of Churches (Nairobi, 1975) in which he called for a renewed recognition of evangelism as “an essential priority.” Renewal of the church, he said on that occasion, “does not come before mission but in mission.” He has served on previous occasions as visiting professor of evangelism both at Bostom University School of Theology and at Perkins School of Theology, Southern Methodist University, Dallas, Texas. In January 1981 Dr. Arias was appointed Professor of Mission and Evangelism at the School of Theology in Claremont, California. Upon his arrival in the United States, the International Bulletin invited Dr. Arias to share with our readers an account of his experience while in prison.